A case study of a contentious education policy : the origins and operations of the bulk funding of teachers' salaries in New Zealand : 1815-2015 : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Education, doctorate in Education, at Massey University, Manawatu, New Zealand - Bayer, Perry David (Massey University, 2015)
Bulk funding as an education policy was immensely controversial, and served to polarise the New Zealand educational community and the wider New Zealand public throughout the eight years of its operation between 1992 and 2000. Even now, fifteen years after its demise, the research undertaken for this thesis shows that bulk funding still has the power to divide people and to excite strong passions. Both the supporters and the opponents of bulk funding tended to demonise the opposite side. Each side would also tend to feel that they had uncovered profound educational truths and that they had the right arguments on their side. Therefore, each side tended to believe that their opponents could negate their arguments only by resorting to ‘slanderous’ speech and to ‘libelous’ writings. Some of the key participants in the bulk funding debate were able to be interviewed for this thesis. It quickly became apparent just how wide the gap between the two parties was during the 1990s and is still today. The research undertaken for this study has discovered that there are often tensions between the central education authorities who devise and impose policy and the local authorities who have to implement it. Bulk funding would seem to be a classic example of the perennial tensions between the centre and the localities. These tensions are a thread that runs throughout the course of New Zealand educational history. Bulk funding did not emerge out of a vacuum. Therefore, it was decided to adopt a “forward moving” historical narrative approach instead of a “history of the present.” My research showed that there have been precursors to this policy right from the time of the first mission schools in the Bay of Islands from 1815 onwards. This study found that these distant historical forebears had to be investigated in order to make more sense of what occurred in the 1990s. Finally, being at a distance from New Zealand and working as a secondary school teacher in Hong Kong where teachers are generally well respected as Chan (2008) noted, it was interesting for me as a ‘distant researcher’ to look back to New Zealand and to the case of bulk funding.
Keywords: Federal aid to education; Teachers' salaries; Education; Finance; Education and state; History; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education